"… if I care about stuff, then other people care about me". Adolescents' experiences of helpful and unhelpful aspects of brief behavioural activation therapy for depression. (17th November 2021) - Lewis-Smith, Iona; Pass, Laura; Jones, Dan J W; Reynolds, Shirley
Abstract: Obective: : Brief Behavioural Activation (Brief BA) is a time limited psychological therapy for the treatment of depression symptoms in adolescents. Research on clients' experiences of the helpful and unhelpful aspects of psychological therapies is important for developing an understanding of the therapeutic process, and for helping to improve interventions and therapists' skills. The aim of this study was to explore 12–19 year old's experiences of the helpful and unhelpful aspects of Brief BA. Method: : Thematic analysis of one-to-one interviews with nine adolescents who had completed Brief BA at school was conducted. Results: : Three main themes relating to the helpful aspects were identified: "self-discovery"; "given the tools to cope and make progress"; "having someone to talk to." One main theme relating to the unhelpful aspects of Brief BA, "discontinuation and maintenance, " was also identified. Conclusions: : Findings indicated that the participants found behavioural activation strategies, identifying values and valued activities, and therapist support to be helpful. The duration of therapy and difficulties in maintaining improvements were identified as unhelpful aspects. Future research is needed to investigate the impact of the timing of the end of therapy and how improvements can be more easily maintained after the end of Brief BA.